Nilai Etnopedagogik Dan Struktur Cerita Dalam Dongéng-Dongéng Cianjur Karya Tatang Setiadi - Dery Maulana Yusuf; Dedi Koswara; Dede Kosasih (Advances In Education Journal, 2026)
Folktales are a form of oral literature that embody cultural values, local history, and character education—all of which are important to pass on to younger generations. This study aims to describe the narrative structure and identify ethnopedagogical values in the book *Asal Usulna Hayam Pelung jeung Dongéng-Dongéng Cianjur Lianna* by Tatang Setiadi. This study employs a qualitative approach using a descriptive-analytical method. The data were sourced from nine folktales in the book, selected through purposive sampling and analyzed using Robert Stanton’s structural theory and the ethnopedagogical concept of Gapura Pancawaluya. Data collection was conducted through literature review using the read-and-note technique, while data analysis involved reduction, classification, interpretation, and drawing conclusions. The results of the study indicate that narrative structural elements—including theme, plot, characters, setting, and point of view—are present in all the fairy tales analyzed and form a cohesive narrative whole. This study also identified six ethnopedagogical values: cageur, bageur, bener, pinter, singer, and pangger. The most prominent values are “bageur” and “bener,” which are reflected in the characters’ behavior through mutual aid, honesty, responsibility, and adherence to social norms. These findings indicate that Tatang Setiadi’s collection of folktales has the potential to serve as both a resource for literary education and a medium for character education rooted in local wisdom